2018
DOI: 10.22146/gamaijb.30136
|View full text |Cite
|
Sign up to set email alerts
|

Customers’ Perceived Fairness; Fast Food Chain Restaurants in Indonesia

Abstract: This study aims to investigate interrelationships among perceived service fairness, emotions, and behavioral intentions in a fast food chain restaurant context. we use terms that are commonly use on the study of fairness or justice perception. This study uses purposive sampling and the survey method to generate our sample which consists of 800 respondents from big cities in Indonesia, namely: Jakarta, Semarang, Surabaya, Medan, and Makassar. The data are analyzed using Structural Equation Modeling (SEM). The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 74 publications
0
6
0
Order By: Relevance
“…The role of price in influencing consumers' attitudes, and in turn affecting customer behaviour, is normal in the restaurant business, despite differences in consumer experience under different circumstances. Price variations in the restaurant business tend to influence customer expectations, evaluation, and decision making (Bhattacharjee, Jahanshahi, Polas, Hossain, & Asheq, 2019; Budiyanti & Patiro, 2018; Namin, 2017; Raju, 2018). The third hypothesis suggests that price perception of Islamic restaurants influences customers' revisit intentions.…”
Section: Literature Review and Development Of Hypothesesmentioning
confidence: 99%
“…The role of price in influencing consumers' attitudes, and in turn affecting customer behaviour, is normal in the restaurant business, despite differences in consumer experience under different circumstances. Price variations in the restaurant business tend to influence customer expectations, evaluation, and decision making (Bhattacharjee, Jahanshahi, Polas, Hossain, & Asheq, 2019; Budiyanti & Patiro, 2018; Namin, 2017; Raju, 2018). The third hypothesis suggests that price perception of Islamic restaurants influences customers' revisit intentions.…”
Section: Literature Review and Development Of Hypothesesmentioning
confidence: 99%
“…In terms of this, when the product fails to live up to expectations (its characteristics don't match the description provided on the website), buyers will be disappointed with the company's service because it will have failed to fulfill the "promise" to send the product with the description provided on the website. The other aspects of service quality, such as the speed of delivery, timeliness, and customer service efforts to help resolve customers' problems, can also play a great role in determining whether the companies value theirs customers or not (Budiyanti and Patiro 2018;Wilson and Christella 2019). Bad or negative service quality can be perceived as a sign that the company doesn't value or it "neglects" its customers, and vice versa.…”
Section: Introductionmentioning
confidence: 99%
“…Research on fairness and discrete emotions suggests a basic model of the relationships among events, justice perceptions and emotions: events lead to justice perceptions and justice perceptions to emotions. Existing research on emotions and fairness relates mainly to outcomes (e.g., Virgolino et al, 2017) or events with both distributive and procedural aspects (e.g., Budiyanti & Patiro, 2018;Yadav & Yadav, 2016). Despite the paucity and limitations of existing research, it provides a foundation for predicting the relationship between emotions and fairness.…”
Section: Organizational Justice and Emotionmentioning
confidence: 99%
“…Additionally, happiness is included in other studies of emotion and fairness (Belén, Vázquez-casielles, & Díaz-martín, 2009;Krehbiel & Cropanzano, 2000). Fairness and justice study in restaurant context also showed the importance of ditributive, procedural, and interactional justice for customers in assesing their needs and satisfaction (Budiyanti & Patiro, 2018). In this study we use happiness as one of the discrete positive emotion.…”
Section: Organizational Justice and Emotionmentioning
confidence: 99%
See 1 more Smart Citation